2021
DOI: 10.1088/1742-5468/abdd17
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Fokker–Planck–Kolmo-gorov equation analysis for asymmetric multistable energy harvesters excited by white noise

Abstract: Due to the broadband response characteristics at low levels of excitations, nonlinear multistable systems have garnered a great deal of attention in the area of energy harvesting. Moreover, various performance enhancement strategies of multistable harvesters have been proposed and discussed extensively for systems with perfectly symmetric potentials. However, it is very difficult or even impossible in practice to modulate a nonlinear system with completely symmetric potentials. Therefore, this paper investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…They found that the number of stable equilibrium positions influences the trivial and nontrivial steady-state solutions. Wang et al [88] investigated stochastic characteristics of asymmetric MEHs and provided an approximate FPK equation. They found that at a constant noise intensity, the probability distribution of velocity response of the harvester is almost unaffected by the potential function shape.…”
Section: Influence Mechanism and Optimizationmentioning
confidence: 99%
“…They found that the number of stable equilibrium positions influences the trivial and nontrivial steady-state solutions. Wang et al [88] investigated stochastic characteristics of asymmetric MEHs and provided an approximate FPK equation. They found that at a constant noise intensity, the probability distribution of velocity response of the harvester is almost unaffected by the potential function shape.…”
Section: Influence Mechanism and Optimizationmentioning
confidence: 99%
“…The harvested electric energy can power low-power online monitoring and sensing devices in practical engineering, such as vehicle tracking, structural health monitoring, environmental monitoring, intelligent building, and aerospace fields [1][2][3]. In the literature, several energy harvesting mechanisms have been introduced to transform such vibration energy into electricity, for instance, electrostatic [4,5], electromagnetic [6,7], piezoelectric [8][9][10][11][12], and magnetostrictive [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as another effective analytical tool of the stochastic system, the path integration procedure was also developed to analyze the probabilistic solution of nonlinear VEH systems [29][30][31]. In addition, Wang et al [32] obtained the probability density functions (PDFs) of asymmetric multistable energy harvesters by the principle of detailed balance that found the design of the asymmetric structure is more conducive to improving the energy harvesting performance relative to the symmetric case. From the above research results, it is not hard to see that those theoretical analysis methods are all established based on all the information of the stochastic model.…”
Section: Introductionmentioning
confidence: 99%